A quadruple-label time-resolved fluorescence immunochromatographic assay for simultaneous quantitative determination of three mycotoxins in grains. Issue 3 (20th December 2019) - Chang, Xiaoxi; Zhang, Yaqing; Liu, Hebing; Tao, Xiaoqi
Abstract : A quadruple-label time-resolved fluorescence immunochromatographic assay (QL-TRFICA) for simultaneous quantitative detection of three mycotoxins (AFB1, ZEN and OTA) in 6 grains (corn, soybean, sorghum, wheat, rice and oats) was established. Abstract : A multiplex quadruple-label time-resolved fluorescence immunochromatographic assay (QL-TRFICA) for simultaneous quantitative detection of aflatoxin B1 (AFB1 ), zearalenone (ZEN) and ochratoxin A (OTA) in grains was established in this paper. This assay was developed based on quadruple-label immunoprobes, one of which was a chicken IgY-specific antibody coupled with time-resolved fluorescent nanobeads (TRFN) for the test C line signal while the other three were specific to AFB1, ZEN and OTA monoclonal antibodies coupled with TRFN for the test T line signal. Quantitative relationships between the concentrations of the three mycotoxins and T/C ratios were established to determine the analyte concentration through a portable multi-channel fluorescence reader. The limits of detection (LODs) for AFB1, ZEN and OTA were 0.04 μg kg −1, 0.20 μg kg −1 and 0.10 μg kg −1 in 6 grains (corn, soybean, sorghum, wheat, rice and oats), respectively. Recoveries ranged from 71.60% to 119.98% at fortified concentrations of LOD, 2LOD and 4LOD, with a coefficient of variation <15%. Analysis of field grain samples by QL-TRFICA was in accordance with that of LC-MS/MS. Therefore, this proposed multiplex QL-TRFICA was a promising method for on-site screening of multiple mycotoxins in grains.